1993
DOI: 10.1007/bf02598288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an educational program on medical students’ conversations with patients about advance directives

Abstract: Advance directives, such as the durable power of attorney for health care (DPAHC), help patients and physicians make end-of-life health care decisions. Medical education should prepare student physicians to be knowledgeable about and comfortable with discussing advance directives. The authors developed an educational module for the third-year medical school curriculum and conducted a randomized trial to evaluate in students its effect on various outcome measures regarding the DPAHC. Over a six-week period, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…The sample in each study varied from 16 to 278, with five [19, 20, 22, 24, 25] including more than 100 participants. Five studies were conducted in the US [17, 20, 22, 25, 26], two in Australia [19, 24], one in the UK [18], one in Canada [23] and one in Korea [21]. The majority of participants were nurses, physicians and medical students.…”
Section: Resultsmentioning
confidence: 99%
“…The sample in each study varied from 16 to 278, with five [19, 20, 22, 24, 25] including more than 100 participants. Five studies were conducted in the US [17, 20, 22, 25, 26], two in Australia [19, 24], one in the UK [18], one in Canada [23] and one in Korea [21]. The majority of participants were nurses, physicians and medical students.…”
Section: Resultsmentioning
confidence: 99%
“… Pre-intervention Patient AD Document Green 2011 [ 34 ] RCT 60 56 Second year medical student in Penn State College of Medicine USA Students help patients create advance directives using a multimedia decision-aid which helps patients clarify their values, explain end-of-life conditions, help users choose and communicate with their surrogate decision makers and translate their wishes and goals. Students using Standard AD Patient Satisfaction with EoL and EoL Care planning Student Knowledge Greenberg 1993 [ 28 ] RCT 46 47 Medical Students beginning their clerkship USA The high-intervention received the same reading as low intervention group as well as a small group seminar on topics of historical development of advance directives, students' experiences with death and dying, contents of a durable power of attorney for health care (DPAHC). Students also viewed a videotape illustrating important aspects of discussing the DPAHC.…”
Section: Resultsmentioning
confidence: 99%
“…Ratings for the overall quality of evidence and effectiveness of the educational interventions can be seen in the GRADE summary of findings table (See Additional file 3 ). Self-Efficacy Eight studies (2 RCTs [ 28 , 29 ], 6 Observational [ 4 , 6 , 30 33 ]), including 522 participants found that EoL communication skills training was associated with improved self-efficacy compared to usual training (SMD 0.57; 95 % CI 0.40–0.75; p < 0.001; very low quality evidence ) . There was no evidence of heterogeneity ( I 2 = 0 %) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data suggest this model may be effective for teaching students the skills of palliative medicine. 26 ' 27 The course stresses to students the importance of physician-patient communication skills and introduces them to several key topics in palliative care. Lectures provide students with the basic facts needed to practice palliative care.…”
Section: Resultsmentioning
confidence: 99%